P. Ramlee’s cinematographic auteurship of cultural values representation in Antara Dua Darjat and Ibu Mertua-Ku - Nurul Ezzati Aisya Mohd Zaki; Wan Hartini Wan Zainodin (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper looks into an investigation on auteur theory’s model of cultural representation through visual narrative employment in P. Ramlee’s two heavy-dramas: Antara Dua Darjat and Ibu Mertua-Ku. By employing a qualitative approach, case study embedded and thematic analyses implored two concepts; film syntax and cultural valuesin both film texts. The findings found that P. Ramlee employed and manipulated visual narrative conventions in his motivated choices of synchronic (space) and diachronic (time) shots in both film texts. In representing cultural values such as communal, brotherhood, responsibility and manners, P. Ramlee portrayed them through distinguishable utilization of cinematography tools – i.e. taking advantage of deep depth of field in layering actions and emphasizing carriers (actors) of values in medium shots. Finally, through the exhaustive exploration of Antara Dua Darjat and Ibu Mertua-Ku’s visual narrative, it was manifested that P. Ramlee fulfilled the characteristics of an auteur as technically competent, infused personality in his works and idiosyncratically instilled interior meanings across his masterpieces. Though studies on P. Ramlee are somewhat saturated, this exploration was initially a challenge to the glorified realm in which P. Ramlee was placed by critics and fans. True to the nature of research, this exploration summed up to an outcome which not only concurs to the filmmaker’s adoring critics but also theoretically accords P. Ramlee into the realm of the auteur.